Annexin 1–nuclear factor‐κB–microRNA‐26a regulatory pathway in the metastasis of non‐small cell lung cancer. Issue 4 (12th February 2019) - Guan, Xiaoying; Fang, Ying; Long, Jie; Zhang, Yajie
Abstract : Background: Annexin 1 (ANXA1) expression is associated with the malignant tumor phenotype, making it an attractive therapeutic target. However, little is known about the regulation of ANXA1 in non‐small cell lung cancer (NSCLC). Methods: We investigated the biological roles of ANXA1 in tumor growth, migration, and invasion, and explored the possibility of ANXA1 as a potential therapeutic target for the treatment of NSCLC. Results: Our findings revealed that ANXA1 enhanced nuclear factor (NF)‐κB activation in NSCLC cells by interaction with inhibitor of NF‐κB kinase complex subunit, IKKγ. We also found that NF‐κB could negatively regulate microRNA (miR)‐26a, and miR‐26a was regulated through the ANXA1–NF‐κB regulatory pathway. NF‐κB activation negatively regulated by miR‐26a was confirmed in NSCLC. Conclusion: Together, these results provide evidence of the mechanisms of the ANXA1–NF‐κB–miR‐26a regulatory pathway in the invasion and migration in NSCLC.